Pemberdayaan Anak-Anak Melalui Program Rutinitas Maghrib Mengaji - Dida, Dida Muhammad Aminulloh; Isye Legita Nurholiyah; Humaeni Sabilah; Busro (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Reciting the Koran is the activity of reading or discussing books related to religious knowledge. However, currently society is experiencing a shift in behavior so that reciting the Koran is increasingly being abandoned. The positive habit of reading the Koran among children is starting to be abandoned by watching television broadcasts, playing games, regardless of time. Therefore, the students of KKN Sisdamas Religious Moderation Group 57 carried out the Maghrib Recitation Routine (RUMAJI) activity, especially in the Al-Mubarokah Mosque, Campakamulya Village. One form of religious activity that can instill morals and spirituality in school-age children is the Maghrib Koran movement, a movement that invites school-age children to fill the time between Maghrib and Isha with Koran activities at the mosque. The aim of this activity is to help the community face the problem of children's low interest in learning about the Koran and Islam. The method used in this service is the sisdamas method or Community Empowerment Based. The result of this empowerment was that the implementation of the Ba'da Maghrib Recitation Movement at the Al Mubarokah Mosque in Campakamulya Village ran smoothly. The recitation includes reading the Al-Qur'an with tajwid, reading Iqra, learning short letters and daily prayers. Apart from that, the results of this empowerment are the emergence of children's motivation to continue reciting the Koran, the growth of children's love for the Al-Qur'an.